The Islamic Education Environment in the Perspective of the Qur'an and Hadith in the Digital Era: A Case Study of SMAN 1 Lawang Kidul - Jossiselfiah, Jossiselfiah; Wulandari, Siska; Damayanti, Anna; Alimron, Alimron; Suharmon, Suharmon (Journal of English Language and Education, 2026)
The rapid development of the digital era has significantly transformed the educational environment, including Islamic education, which faces the challenge of balancing technological advancement with the strengthening of Islamic values. An Islamic educational environment grounded in the Qur’an and Hadith plays a strategic role in shaping students’ character so that they maintain noble morals amid the dynamics of digitalization. This study aims to analyze the concepts, principles, and implementation of the Islamic educational environment from the perspective of the Qur’an and Hadith in the digital era through a case study at SMAN 1 Lawang Kidul. This research employs a qualitative approach with a case study design. The research subjects consist of the school principal, Islamic Education (PAI) teachers, and students. Data were collected through in-depth interviews, participant observation, and documentation studies, and analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings reveal that the Islamic educational environment at SMAN 1 Lawang Kidul has integrated Qur’anic and Hadith-based values into the physical, social, and academic dimensions of the school through religious habituation programs, teacher role modeling, and the educational use of digital media. However, challenges persist, particularly regarding limited supervision of students’ use of digital technology outside formal learning activities. Overall, this study demonstrates that an Islamic educational environment rooted in the Qur’an and Hadith remains relevant and adaptive in responding to the challenges of the digital era, while also highlighting the need for more comprehensive strategies to strengthen digital ethics and supervision in public schools.